2016
DOI: 10.4311/2015mb0131
|View full text |Cite
|
Sign up to set email alerts
|

Culturable bacteria associated with the caves of Meghalaya in India contribute to speleogenesis

Abstract: The caves of Meghalaya in India are some of the longest caves in the subcontinent that have so far received negligible attention of geomicrobiologists. The present work was undertaken to discover and explore bacterial biofilms of various textures and colors from five caves of Meghalaya in North-East India. There are no previous specific scientific investigations from three of the studied caves. Thirty-two different culturable bacterial species belonging to sixteen different genera were characterized. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…Proteobacteria phylum was dominated by the class Gammaproteobacteria with Pseudomonas sp. observed as the major genera in accordance to previous studies (Barton et al, 2004;Banerjee & Joshi, 2016;Yasir, 2018). Proteobacterial population seldom observed to be the dominant class in most of the cave bacterial diversity studies with the majority of the bacterial population has been shown as Actinobacteria (Axenov-Gribanov et al, 2016;Ghosh et al, 2016Ghosh et al, , 2017Lavoie et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Proteobacteria phylum was dominated by the class Gammaproteobacteria with Pseudomonas sp. observed as the major genera in accordance to previous studies (Barton et al, 2004;Banerjee & Joshi, 2016;Yasir, 2018). Proteobacterial population seldom observed to be the dominant class in most of the cave bacterial diversity studies with the majority of the bacterial population has been shown as Actinobacteria (Axenov-Gribanov et al, 2016;Ghosh et al, 2016Ghosh et al, , 2017Lavoie et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, high and optimal GC content of prokaryotes led to the high thermal adaptability was also reported elsewhere (45). The evidence of biofilm formation in electron micrograph by of the novel Bacillus velezensis AG20 was also a feature of cave microbes similarly reported earlier by Banerjee and coworker (2, 7). Thermostable and thermophilic xylanases have much industrial significance.…”
Section: Discussionsupporting
confidence: 84%
“…From the caves Krem Soitan, Krem Mawpun, and Krem Lawbah, 113 bacterial isolates were identified and majority belonged to the genus Bacillus, Rummeliibacillus, Staphylococcus, and Brevibacterium (6). In another report Banerjee and coworkers reported the abundance of the genera Bacilllus and Pseudomonas from Krem Mawsmai, Krem Mawmluh and Krem Mawjymbuin caves of East Khasi Hills, Meghalaya, India (7). Not many reports have been entailed since then about the geo-microbial aspects from the caves of Meghalaya, India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, another bacterial diversity study from the bacterial biofilms explored from five caves from the Meghalaya in India, and identified Pseudomonas spp. as the major genus [36]. We found the presence of Achromobacter spp., although other studies have rarely identified it.…”
Section: Discussionmentioning
confidence: 68%